Trace analysis using an Event-driven Interval Temporal Logic - Gallardo-Melgarejo, María del Mar; Panizo-Jaime, Laura (Springer Nature, 2020)
Nowadays, many critical systems can be characterized as hybrid ones, combining continuous and discrete behaviours that are closely related. Changes in the continuous dynamics are usually fired by internal or external discrete events. Due to their inherent complexity, it is a crucial but not trivial task to ensure that these systems satisfy some desirable properties. An approach to analyze them consists of the combination of model-based testing and run-time verification techniques. In this paper, we present an interval logic to specify properties of event-driven hybrid systems and an automatic transformation of the logic formulae into networks of finite-state machines. Currently, we use Promela/Spin to implement the network of finite-state machines, and analyze non-functional properties of mobile applications. We use the TRIANGLE testbed, which implements a controllable network environment for testing, to obtain the application traces and monitor network parameters.
Keywords: Informática - Aplicaciones; Soporte lógico - Verificación; Hybrid systems; Logic